Agronomical and Physiological Characters of Kaffir Lime (Citrus hystrixDC) Seedling under Artificial Shading and Pruning - Roedhy Poerwanto, Rahmat Budiarto; Efendi, Andria Agusta, Edi Santosa, Darda (Emirates Journal of Food and Agriculture, 2019)
Kaffir lime (Citrus hystrix DC) is a minor citrus and its leaves are locally used for spices and essential oils. This study aimed to evaluate agronomical and physiological characters of kaffir lime seedling under modified cultural practices in order to improve leaf production. Shading and pruning were applied on five-month-old seedling during the rainy season, November 2017 to March 2018 in Bogor, Indonesia. The results showed that shading significantly improved the plant growth by 84%, and leaf number by 37%. Pruning treatment reduced the plant height by 8% and increased the shoot number by 20%. However, leaf production was more influenced by shading rather than pruning, with an increase for about 59% than control. This study also revealed a significant improvement on photosynthetic rate, stomatal conductance and water use efficiency on shaded lime for about 13%, 8% and 14%, respectively. Leaf pigment was also altered in response to shading, i.e the increasing chlorophyll B by 23% and the reduction anthocyanin by 38% on shaded lime. Mild shading with 24% light reduction is recommended to gain the leaf production of kaffir lime seedling.